Where am I in STEM? Critiquing STEM Through Lived Experience as a Science Education Researcher - Stapleton, Sarah Riggs (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
This critique of STEM comes from a feminist, embodied approach, which takes into account how my positionality in relation to the acronym intersects with my lived experience and perspective. My hope is that speaking from personal experience will help initiate fissures and dissonance about STEM discourse, in chorus with other positions and arguments, to critically question and hopefully dislodge the STEM acronym as a hegemonic, pervasive, and unexamined construct. I offer my experiences as a way of joining others in open critique of an often unquestioned yet neoliberal dominating force in science education. My lived experiences (and frustrations) with STEM are numerous. I condense these experiences into four episodes: the STEM academic job interview, the STEM education meeting, dissonance between STEM and my gendered identity, and exclusion of my humanist science research interests by the STEM acronym.